Human Chorionic Gonadotropin-Mediated Immune Responses That Facilitate Embryo Implantation and Placentation - Schumacher, Anne; Zenclussen, Ana C. (Frontiers in Immunology, 2019)
Human chorionic gonadotropin (hCG) serves as one of the first signals provided by the embryo to the mother. Exactly at the time when the first step of the implantation process is initiated and the blastocyst adheres to the maternal endometrium, the embryonic tissue starts to actively secrete hCG. Shortly thereafter, the hormone can be detected in the maternal circulation where its concentration steadily increases throughout early pregnancy as it is continuously released by the forming placenta. Accumulating evidence underlines the critical function of hCG for embryo implantation and placentation. hCG not only regulates biological aspects of these early pregnancy events but also supports maternal immune cells in their function as helpers in the establishment of an adequate embryo-endometrial relationship. In view of its early presence in the maternal circulation, hCG has the potential to influence both local uterine immune cell populations as well as peripheral ones. The current review aims to summarize recent literature on the participation of innate and adaptive immune cells in embryo implantation and placentation with a specific focus on their regulation by hCG.